2022
DOI: 10.3390/ph15020228
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Cinnamic Acid-Based Antimicrobials

Abstract: (1) Background: The main antimicrobial resistance (AMR) nosocomial strains (ESKAPE pathogens such as Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) are the most widespread bacteria in cutaneous infections. In this work, we report the synthesis, in silico skin permeability prediction, and antimicrobial, antibiofilm, and wound healing properties of novel cinnamic acid-based antimicrobials (DM1–11) as novel antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The most isolated organisms in surgical site infections are S. aureus, coagulase-negative staphylococci, Enterococcus spp., and Escherichia coli. An increasing number of SSIs are attributable to antibiotic-resistant pathogens, such as methicillin-resistant S. aureus (MRSA) or Candida albicans [ 67 , 68 , 69 ]. To address these challenges, extensive antibacterial and in vivo studies are required to understand the impact of antibiotic-drug–NP-coated sutures during the treatment of SSIs, which are currently ongoing in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…The most isolated organisms in surgical site infections are S. aureus, coagulase-negative staphylococci, Enterococcus spp., and Escherichia coli. An increasing number of SSIs are attributable to antibiotic-resistant pathogens, such as methicillin-resistant S. aureus (MRSA) or Candida albicans [ 67 , 68 , 69 ]. To address these challenges, extensive antibacterial and in vivo studies are required to understand the impact of antibiotic-drug–NP-coated sutures during the treatment of SSIs, which are currently ongoing in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of Madhugrit might be due to the presence of a plethora of phytochemicals namely ellagic acid, coumarin, cinnamic acid, and palmatine which are known to enhance wound healing (69)(70)(71)(72). Also, it has been reported that cinnamic acid-based formulations in addition to wound healing, have antimicrobial properties as well (73). This further augments the therapeutic potential of Madhugrit.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that Car possesses a wide range of properties, including antimicrobial and anti-inflammatory activity [ 30 ]. In the last decade, medicinal chemistry-based approaches (prodrugs, codrugs, derivatives, and/or hybrids) were also used by us to improve the efficacy and pharmacokinetic properties of Car [ 31 , 32 , 33 , 34 , 35 ]. Using these strategies, Car was linked to amino acids (to improve water solubility) [ 31 ], cinnamic acid derivatives (to obtain topic drugs for the treatment of skin infections) [ 32 ], antioxidants (to enhance its potency as an antimicrobial and antifungal drug) [ 33 ], and benzyl moiety, especially meta- or para-substituted (to obtain dual inhibitors of H. pylori strains and AGS cell proliferation) [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, medicinal chemistry-based approaches (prodrugs, codrugs, derivatives, and/or hybrids) were also used by us to improve the efficacy and pharmacokinetic properties of Car [ 31 , 32 , 33 , 34 , 35 ]. Using these strategies, Car was linked to amino acids (to improve water solubility) [ 31 ], cinnamic acid derivatives (to obtain topic drugs for the treatment of skin infections) [ 32 ], antioxidants (to enhance its potency as an antimicrobial and antifungal drug) [ 33 ], and benzyl moiety, especially meta- or para-substituted (to obtain dual inhibitors of H. pylori strains and AGS cell proliferation) [ 34 ]. In this context, considering the wide potential of this terpenoid as a pharmaceutical compound, the aim of this work was to develop a small series of Car derivatives ( CD1-3 ) with anti-adipogenic and anti-inflammatory properties endowed with reduced side effects typical of NSAIDs.…”
Section: Introductionmentioning
confidence: 99%